Family Day Care Educators' Knowledge, Confidence and Skills in Promoting Children's Social and Emotional Wellbeing: Baseline Data from Thrive. Issue 3 (September 2014) - Davis, Elise; Corr, Lara; Ummer-Christian, Rahila; Gilson, Kim-Michelle; Waters, Elizabeth; Cook, Kay; Harrison, Linda; Herrman, Helen; Mackinnon, Andrew; Sims, Margaret; Mihalopoulos, Cathrine; Marshall, Bernie
THIS PAPER PRESENTS BASELINE data from Thrive, a capacity-building program for family day care educators. Educators completed a self-report survey assessing knowledge and confidence in promoting children's social and emotional wellbeing. An in-home observation was used to assess care quality. Twenty-four educators responded to the survey (40 per cent response rate). They had an average of nine years' experience and 82 per cent held childcare qualifications. Educators reported knowledge of, on average, three early signs of social and emotional problems in children, three risk factors and two protective factors. Using a scale from 0–10, mean educator confidence levels ranged from an average of 6.69 to 7.25. Quality of care ratings were moderate. Although educators had a good understanding of children's social and emotional wellbeing, the study identified opportunities for significant changes in the quality of the educators' interactions with children in their care and their professional development.